OCCUPATIONAL ALLERGIC CONTACT DERMATITIS TO MERCAPTOBENZOTIAZOL - Araújo, Catarina (2015)
Introduction: Allergic contact dermatitis to mercaptobenzothiazole and its derivatives has been increasingly recognized in industrialized countries because of their widespread use in polymerization of synthetic rubber. The authors describe two clinical cases with relevant occupational exposure.Case reports: A 46 year-old male patient, with an eight month pruritic dermatitis, limited to the wrists, refractory to high potency topical corticosteroid and oral antihistamine. Physical examination showed erythematous-violaceous infiltrated plaques and excoriated erythematous papules on both wrists. Prick tests and RAST to latex were negative. Epicutaneous tests were performed with basic series from Portuguese Contact Dermatitis Group, rubber and glue series and fragments of the sleeve and it was found positivity for mercaptobenzothiazole (++), mercapto mix (++) and elastic band of gloves in reading at 72h and at 7 days. A 61 years old non atopic man, woodworker, with a 12- month history of itching, erythema, infiltration of genius region of face and extension to posterior cervical region.Epicutaneous tests were performed with basic series from Portuguese Contact Dermatitis Group, rubber and glue series, cosmetics series and fragments of the protection mask work and it was found positivity for mercaptobenzothiazole (++), mercapto mix (++) and elastic band of mask (++) in reading at 72h and at 7 days.Discussion: Despite being well known allergens, mercaptobenzothiazole and its derivatives may be present in other sources of exposure to rubber like elastic fabric in clothing. Once the worker sensitized, it can be an important cause of disability in an occupational and personnal setting.